‘TESTAMENTUM PORCELLI’ - Dzikowski, Andrzej; Jurewicz, Aldona Rita; Molisak, Gabriela (Zeszyty Prawnicze, 2017)
The ‘Testamentum Porcelli’ Summary This paper is a translation and commentary of the anonymous fourth-century pamphlet referred as the Testamentum Porcelli. Notwithstanding the humorous nature of the work, it became the subject of scholarly dispute focused on its actual meaning and potential author. The main concepts, together with the characters associated with them, are presented in footnotes and commentaries with an explanation of particular issues, e.g. the structure of the text, Roman law, and allusions to pagan festivals and customs.